KARAKTERISTIK SPENT ORE PROSES HEAP LEACH SINGLE STACKING BERDASARKAN UJI XRD, XRF DAN MIKROSKOP BIJIH TERHADAP POTENSI PEMBENTUKAN AIR ASAM TAMBANG (Jurnal Geomine, 2016)
Gold processing technology with a single heap leach cyanidation method of stacking is sprinkled with the processing of the pile of ore cyanide solution to dissolve the precious metals without dissolving impurities. Gold processing waste rock (spent ore) containing sulfide minerals can be potentially in the formation of acid mine water so keep in mind the influence of spent ore mineralogy of gold to the formation of acid mine water. This study aims to: (1) determine the characteristics of spent ore mineralogy of rocks based on test geochemical and petrological rock, (2) the effect of the mineralogy of the formation of acid mine water single-process heap leach stacking. Handling of acid mine drainage initial step that must be done is to characterize the mineralogy of rocks spent ore. The method used to determine the mineralogy of rocks is to test the mineralogy by XRD analysis (X-ray Diffractions), analysis of XRF (X-Ray fluorescence), and the ore microscope observation. The analysis showed that the mineralogy spent gold ore leach process head affect the formation of acid mine water.